Indoor air quality assessment in the air traffic control tower of the Athens Airport, Greece - Helmis, C.G.a; Assimakopoulos, V.D.b; Flocas, H.A.a; Stathopoulou, O.I.a; Sgouros, G.a; Hatzaki, M.a (Environmental Monitoring and Assessment, 2009)
In this study, an assessment of indoor air quality (IAQ) and thermal comfort in the Athens Traffic Control Tower (ATCT) offices of Hellinicon building complex, which is mechanically ventilated, is presented. Measurements of PM 10, PM 2.5, TVOCs and CO 2 concentrations were performed during three experimental cycles, while the Thom Discomfort Index was calculated to describe the employees’ feeling of discomfort. The aim of the first cycle was to identify the IAQ status, the second to investigate the effectiveness of certain measures taken, and the third to continuously monitor and control IAQ. During the first two cycles, daily spot measurements of TVOCs and CO 2 were performed at various indoor locations and at the respective outdoor air intake positions, in addition with mean 24-h spot measurements of indoor PM 10 and PM 2.5. Results revealed that pollution levels vary according to the occupancy and the kind of activity. Following that, an automated system (IMAS) was designed and employed to continuously monitor indoor and outdoor CO 2, TVOCs, temperature and relative humidity. The ultimate scope was to control the IAQ and offer acceptable comfort conditions to the employees, whose work is of special nature and extremely demanding. Intervention scenarios were formulated and applied to the system to improve indoor conditions, when and where necessary. Regarding the third cycle, 1-year measurements collected from the system to examine its effectiveness. While it was shown that discomfort may be attributed to co-existence of unsatisfactory thermal comfort conditions and IAQ, usually the sole predominant factor of discomfort feeling is thermal comfort. © Springer Science+Business Media B.V. 2008.
Keywords: Air Pollutants; Air pollution; air pollution control; Air quality; air quality control; air sampling; air temperature; Air traffic control; airport; article; Athens [Attica]; Atmospheric humidity; Attica; Aviation; Buildings; carbon dioxide; CO 2; concentration (composition); Control towers; controlled study; Environmental Monitoring; Eurasia; Europe; Flow of gases; Greece; human; Humans; humidity; Humidity control; Indoor; indoor air; Indoor air pollution; Indoor air quality; job satisfaction; Measures; Occupational; occupational exposure; Offices; performance assessment; Permanent magnets; Personnel; PM 10 and PM 2.5; pollution monitoring; quantitative analysis; Relative humidity; Seasons; Sick Building Syndrome; Southern Europe; temperature; temperature measurement; Thermal comfort; Towers; TVOC S; Ventilation; Weather; workroom air